SISTEM PROTOTYPE KEBOCORAN GAS LPG MENGGUNAKAN ESP8266 DAN API TELEGRAM DENGAN METODE FUZZY - Yustian Ario Susanto; Dendy Kurniawan; Ahmad Ashifuddin Aqham; Edy Siswanto; Bagus Sudirman (Informatika: Jurnal Teknik Informatika dan Multimedia, 2025)
Although LPG is widely utilized in homes and restaurants, gas leaks pose a significant risk of deadly fire and explosion.   The objective of this project is to combine the Mamdani fuzzy logic technique, MQ-6 gas sensor, flame sensor, and ESP8266 microcontroller to create an Internet of Things (IoT)-based prototype system for detecting LPG leaks.   The system includes a servo motor, LCD, relay, buzzer, and real-time notifications using the Telegram app.   The research process employed was prototyping, which encompasses requirements analysis, design, implementation, and testing of hardware and software.   In order to classify the environment into three safety conditions—danger, alert, and safe—sensor data from gas and flame detectors was interpreted using Mamdani fuzzy logic.   The experiment results showed that the system could detect changes in gas concentration and the presence of fire in real time with speed and accuracy.   The fuzzy logic approach makes decisions more smoothly than conventional logic, allowing for early identification even at low gas levels.   Telegram messages were effective in providing users with timely alerts to take preventative action.   In conclusion, by serving as an early warning system for LPG leaks, the proposed prototype system increases safety in residences and food stalls.  Additionally, it could serve as a foundation for the creation of more comprehensive IoT-based fire detection systems.